Profil Histologi Duodenum Berbagai Itik Lokal Di Kabupaten Semarang - Apriliyani, Nur Indah; Djaelani, Muhammad Anwar; Tana, Silvana (Bioma : Berkala Ilmiah Biologi, 2016)
Local duck had been widely cultivated not only as a producer of eggs processed as salted egg but also there are cultivated as broiler ducks. The efforts to improve the productivity of ducks can be seen from the effectiveness of the process of absorption of nutrients in the duodenum, so the use of energy in the metabolic process can be optimized for adding mass and volume of the cell. This study aims to determine the duodenum profile of the histological structure covered the lumen diameter, villous height and number of goblet cells of Magelang ducks, Tegal ducks and Pengging ducks .This study used a completely randomized design (CRD) with three treatments (Magelang ducks, Tegal ducks and Pengging ducks) and 6 replications. The measured variable was the long intestine tenue, lumen diameter, villous height and number of goblet cells. Data were analyzed using analysis of variance (ANOVA) with a differentiation factor was the type of duck. The realdifferences data were analyzed using advanced test of Duncan at the level of 95%. The results showed long intestine tenue, lumen diameter and height of the villi were not significantly different at each Magelang ducks, Tegal ducks, Pengging ducks. The number of goblet cells in Magelang ducks and Tegal ducks showed significantly different, but not on Pengging Ducks. The conclusion of the study was the length of the intestine tenue, lumen diameter and height of villous had no real effect on three types of ducks. Keywords: Local ducks, duodenum, histological